Requerimento de treonina para jundiá (Rhamdia quelen) na fase inicial - Flores, Daniel Prois (2015)
In this trial the requirement of threonine for the jundiá (Rhamdia quelen) was studied during the initial growth phase. Therefore a dose response experiment with five threonine inclusion levels (1.6, 2.2, 2.8, 3.4, 4.0% crude protein (CP)) and four replications was performed. The mixed diets were isonitrogenous (37% CP) and isocaloric (3400 kcal / kg estimated digestible energy). Juvenile jundiás (initial weight 4.47 ± 0.39 g and 8.16 ± 0,49cm length) were subjected to 70 experimental days, fed three times a day until apparent satiation, and their consumption calculated on a daily basis. Water quality parameters levels were kept optimal for the specie. Every twenty one days biometry was performed to evaluate the parameters of weight, weight gain, specific growth rate and feed conversion ratio. Body composition, nutrients deposition, metabolic, and enzymatic parameters were evaluated at the beginning and end of the trial. The data were submitted to normality test, analysis of variance, polynomial regression, and segmented regression. Then was chosen the analysis that best fits the data by comparing the residual error. The parameters of hepatossomatic index, mineral matter, and CAA, were higher in treatment with 1.6% of threonine in the diet. Based on the biomass parameters, relative weight gain, specific growth rate, and total weight gain, the appropriate level of threonine for catfish in that weight stage is 2.45% of threonine of the gross protein in the diet.